2018
DOI: 10.1007/s00170-018-2073-z
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art review on vibration-assisted milling: principle, system design, and application

Abstract: Vibration-assisted machining (VAM) is an external energy assisted machining method to improve the material removal process by superimposing high frequency and small amplitude vibration onto tool or workpiece motion. VAM has been applied to several machining processes, including turning, drilling, grinding, and more recently milling, for the processing of hard-to-machine materials. This paper gives a critical review of vibration-assisted milling (VAMilling) research. The basic kinematic equations of 1D and 2D V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 77 publications
(94 reference statements)
0
20
0
1
Order By: Relevance
“…However, according to the crest from the surface, it has been removed through introducing vibration-assisted by the alternating cycle phenomenon [18]. Thus, it is assumed that a high-quality surface can be achieved by the vibratory workpiece.…”
Section: Design Of Proposed 3-dof Rotary Vibration-assisted Micropmentioning
confidence: 99%
“…However, according to the crest from the surface, it has been removed through introducing vibration-assisted by the alternating cycle phenomenon [18]. Thus, it is assumed that a high-quality surface can be achieved by the vibratory workpiece.…”
Section: Design Of Proposed 3-dof Rotary Vibration-assisted Micropmentioning
confidence: 99%
“…The first two types are described by equations (1)- (8). Type I criterion is satisfied when the cutting direction component of the relative velocity between tool and workpiece is opposite to the tool rotation direction [1,23]. As shown in Fig.…”
Section: Force Predictive Model In Ultrasonic Vibration-assisted Millmentioning
confidence: 99%
“…Micro-scale high frequency vibration with small amplitude is applied on the tool or workpiece to realize the tool-workpiece separation during the milling process. Several research studies have concluded that the tool-workpiece separation in ultrasonic vibration-assisted milling is the main reason for several benefits including improved surface quality [1], lower machining forces, and extended tool life [2]. This tool-workpiece interaction is microscopically non-monotonic which facilitates chip separation and therefore reduces machining forces.…”
Section: Introductionmentioning
confidence: 99%
“…VAM has been applied to various machining processes, including turning, drilling, grinding, and more recently milling, for the processing of hard-to-. [1], [2] machine materials LITERATURE SURVEY [3] Naresh Kumar Maroju, Krishna P. Vamsi & Jin Xiaoliang, 2017 has studied the mechanics of orthogonal turning with lowfrequency (less than 1000 Hz) vibration assistance. Finite element simulations are conducted to predict and compare the stresses, forces, and temperature between conventional turning (CT) and low frequency vibration-assisted turning (LVAT).…”
Section: Introductionmentioning
confidence: 99%